The Dystopian Impulse in James Dashner’s The Maze Runner (2009): The Intersectionality between Order and Chaos - Bederina ,Sarah; Mouissa ,Fattoum (Faculty of Letters and Foreign Languages Department of English, 2019)
The present work explores the inclusion of dystopian elements in addition to the projection of both themes of order and chaos in James Dashner’s work The Maze Runner. The novel recorded the practices of totalitarianism as well as the depiction of a chaotic world where control was the central key. Consequently, The Maze Runner highlighted a variety of components that are pertinent to dystopian writings namely the will to control, the nightmarish setting, the dehumanizing milieu, and the themes of fear and bravery. Control was viewed through the hegemonic practices of WICKED that designed a terrifying maze as a way to dehumanize the boys. This control evoked, as a result, fear within them and created the urgent need for bravery as a way to escape the Maze. This research focuses, equally, on the depiction of Order and Chaos within the heart of the literary work. Order, was presented through the ability of the Gladers to create an organized society and a set of rules; whereas chaos was represented in all what contradicted to this order. The work attempts, accordingly, to create an intersectionality that links the two themes to each other in order to show that they cannot be separated. The intersectionality was consequently established on the basis that the Gladers could not keep order and as a result, they embraced chaos by breaking the rules and chaos in return affected the calm atmosphere of the Glade and deteriorated it.